Perforated Appendicitis with Generalized Peritonitis in a Patient with Situs Inversus Totalis: A Case Report and Literature Review - Thomas Anggara (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: Situs inversus totalis (SIT) is a rare congenital condition characterized by the mirror-image transposition of thoracic and abdominal organs. Its co-occurrence with acute appendicitis, one of the most common surgical emergencies, presents a significant diagnostic challenge due to the atypical, left-sided clinical presentation. This can lead to diagnostic delays and an increased risk of complications. CASE ILLUSTRATION: A 40-year-old male presented to the emergency department with a three-day history of generalized abdominal pain that originated in the left lower quadrant (LLQ). Physical examination revealed tachycardia and signs of generalized peritonitis. Laboratory investigations showed marked leukocytosis. A chest radiograph incidentally revealed dextrocardia, raising suspicion for situs inversus. A subsequent abdominal ultrasound confirmed the transposition of visceral organs and identified findings suggestive of acute appendicitis in the LLQ. An emergency exploratory laparotomy was performed, which confirmed a perforated, gangrenous appendix located in the left iliac fossa, with approximately 200cc of purulent fluid in the peritoneal cavity. An appendectomy was performed, and the patient experienced an uneventful post-operative recovery. DISCUSSION: The patient's initial presentation with LLQ pain is a classic "mirror image" of typical appendicitis, highlighting the critical importance of considering anatomical variations in the differential diagnosis of abdominal pain. The diagnostic pathway, initiated by the serendipitous finding of dextrocardia, underscores the pivotal role of basic and advanced imaging in unmasking the underlying condition and facilitating timely surgical intervention, thereby preventing further morbidity. CONCLUSION: Although exceedingly rare, left-sided appendicitis in patients with situs inversus must be included in the differential diagnosis for patients presenting with LLQ pain. A high index of clinical suspicion, coupled with prompt and appropriate imaging, is paramount to avoiding diagnostic delays and reducing the risk of severe complications such as perforation and generalized peritonitis.